Patient-Reported Outcomes Measurement in Radiation Oncology: Interpretation of Individual Scores and Change over Time in Clinical Practice - Jae-Yung Kwon; Lara Russell; Theresa Coles; Robert J. Klaassen; Kara Schick-Makaroff; Kathryn M. Sibley; Sandra A. Mitchell; Richard Sawatzky (Current Oncology, 2022)
Tools for measuring patients’ perceived health and quality of life, such as patient-reported outcome measures (PROMs), inform clinical decisions for patients requiring radiation therapy. However, there may be inconsistencies in how patients interpret and respond to PROMs due to cultural, environmental, personal, or experiential factors. Differential item functioning (DIF) and response shift (RS) refer to differences in the meaning of PROMs between patients or over time (respectively). DIF and RS can threaten the accurate interpretation and use of PROMs, potentially resulting in erroneous conclusions about effectiveness, and flawed individual-level clinical decision-making. Given the empirical evidence of DIF and RS, we aim to review clinical implications and solutions for addressing DIF and RS by providing vignettes from collaborative examinations with workshop participants, as well as the literature. By making these methodological concepts accessible and relevant, for practice, clinicians may feel more confident to ask clarifying questions of patients when PROM scores and the contextual patient information do not align. PROM scores need to be interpreted via dialogue with the patient to avoid misinterpretation due to DIF and RS, which could diminish patient–clinician communication and impede shared decision-making. This work is part of an interdisciplinary knowledge translation initiative focused on the interpretation of PROM scores by clinically-oriented audiences.